Immune globulin subcutaneous, human 20% solution (Xembify®), a new high concentration immunoglobulin product for subcutaneous administration. (March 2020) - Alonso, William; Vandeberg, Pete; Lang, John; Yuziuk, Jeffrey; Silverstein, Rebecca; Stokes, Kenya; McBride, Dennis; Cruz, Maria; Burns, Doug; Merritt, W. Keither; Willis, Todd; Jorquera, Juan I.
Abstract: Immune globulin subcutaneous, human 20% solution (IGSC-C 20%, Xembify®)—a new 20% immunoglobulin (IgG) liquid product for subcutaneous (SC) administration—has been developed by Grifols. The IGSC-C 20% formulation is based on knowledge acquired from the formulation of Immune Globulin Injection (Human), 10% Caprylate/Chromatography Purified (IGIV-C 10%, Gamunex®-C). The protein concentration was increased from 10% to 20% to provide a smaller volume for SC administration. The IGSC-C 20% manufacturing process employs the same caprylate/chromatography purification steps as IGIV-C 10%, with the addition of an ultrafiltration step so that the product can be formulated at a higher protein concentration. IGSC-C 20% has been produced at full industrial scale to support clinical studies and licensure. These batches were characterized using a comprehensive panel of analytical testing. The new IGSC-C 20% product maintains the same composition, neutralizing activity, purity, and quality characteristics found in IGIV-C 10%.